Competitive deposit rates and bank service charges - Juha Tarkka (Bank of Finland, 1989)
This paper presents a partial equilibrium model of the determination of deposit rates of interest and bank service charges in a competitive banking industry. It is shown that uncertainty regarding the future use of transactions services can cause a positive. interest rate margin on deposits, and below-cost pricing of transactions services. This contrasts with existing literature which has explained the existence of "implicit interest" as a consequence of interest rate ceilings or non-neutral taxation.
URN:NBN:fi:bof-201807301772
Keywords: 330